MODELS IN DIGITAL FORMAT FOR THE STUDY OF THE ORIGIN OF THE COELOM - Armiñana García, Rafael (2021)
The work consisted of the design, elaboration and proposal of models with the use of Information andCommunication Technologies (ICT), to contribute to the study of the origin of the coelom in animals withbilateral symmetry in the teaching-learning process of Biology 2, in high school. Several methods ofinformation gathering and processing were used, which allowed verifying the evident deficienciesregarding the use and elaboration of models in digital format for the study of the origin of the coelom in the teaching-learning process of this subject. A total of three models, related to the acoelomate, pseudocoelomate and coelomate condition in bilaterally symmetrical animals were built in electronic format. The constructed models were introduced in the teaching - learning process of Biology 2 from the course 2019 - 2020. The models proposed, until their implementation, were assessed by expert criteria that considered them relevant. The criteria offered by teachers and students after applying the selectedmethods to them were also taken into consideration. The effectiveness of the models was also madeevident taking into consideration the results obtained by the students once the pedagogical test was applied. It is concluded that the thematic approached is important and coincides with the transformations that are carried out in the National Education System in Cuba and in particular in the 8th grade of secondary 4education.